The Role of Nonverbal Communication in Enhancing Reading Comprehension for EFL Students in Vietnamese Classrooms - Huong Hien Thi Nong (Vietnam Journal of Education, 2025)
Nonverbal communication, including gestures, facial expressions, eye contact, and body movements, serves as a valuable tool in English as a Foreign Language classrooms by reinforcing language comprehension and fostering an engaging learning environment. This study explores the role of nonverbal communication in enhancing reading comprehension among Vietnamese students learning English as a Foreign Language. A mixed-methods approach is employed, incorporating both quantitative and qualitative data gathered through observations and student questionnaires in the English as a Foreign Language classroom setting at a Vietnamese university. The findings indicate that gestures and facial expressions are particularly effective in aiding vocabulary comprehension and interpreting the emotional tone of reading material. Eye contact and body movements contributed significantly to maintaining focus and creating a supportive atmosphere that encourages student participation. These insights suggest that integrating nonverbal communication strategies into reading instruction can make language more accessible and relatable, enhancing students’ comprehension and engagement. This study underscores the importance of nonverbal cues in English as a Foreign Language pedagogy and offers recommendations for further research on nonverbal communication’s role across different language learning skills.